A Pilot Study of Palliative Care Provider Self-competence and Priorities for Education in Kenya. Issue 4 (August 2015) - Sedillo, Rebecca; Openshaw, Maria Mia; Cataldo, Janine; Donesky, DorAnne; Boit, Juli McGowan; Tarus, Alison; Thompson, Lisa M.
Abstract : This study explored palliative care provider self-competence and priorities for future education in an inpatient hospice setting in Kenya. Self-competence scores for clinical skills and patient and family communication skills were hypothesized to differ according to provider type. A descriptive, cross-sectional study design was piloted at Kimbilio Hospice, a 26-bed rural, inpatient facility in Kenya. A quantitative survey instrument entitled, "Self assessment of clinical competency and concerns in end-of-life care, " was administered to participants. Survey responses were collected from 5 clinical staff, 11 caregivers, and 8 support staff. Data were analyzed using Kruskal-Wallis test to compare between mean scores. Statistically significant differences were found in 5 self-competence variables: performing a basic pain assessment, use of oral opioid analgesics, assessment and management of nausea/vomiting and constipation, and discussing an end-of-life prognosis with a patient's family member ( P < .05). Sixteen participants (66%) selected pediatric palliative care as their top priority for future education. The findings support the hypothesis that palliative care providers have varying levels of self-competence. Improving education to build palliative care competencies in adult and pediatric palliative care in sub-Saharan Africa is recommended.